REPRESENTATION OF POWER DYNAMICS IN DIALOGUES IN THE FILM CRASH OUT - Ramadhianti, Agustina; Sofiani, Yulia; Somba, Sugianti (IdeBahasa, 2025)
Through Norman Fairclough's Critical Discourse Analysis or CDA approach, the current research analyzes how words and sentences are used in the film Crash Out. This research aims to highlight three areas of analysis, namely textual dimensions, discourse practices, and social practices, which are used in this qualitative descriptive research. Direct cinema analysis and voice transcriptions containing temporal, symbolic, and ideological content were used to gather data. In addition to information gathering, language aspects such as diction, coherence, irony, and pauses in speech were also observed. The findings illustrated how language was used to build narrative tension, demonstrate control over power, and change the way time was perceived in the film Crash Out. The main character was supported by a symbolic power structure constructed through linguistic features such as temporal repetition and time metaphors. Besides being a tool for interpersonal interaction, language functions as a control mechanism, a delay mechanism, and a technique for framing reality. In the film Crash Out, the power of words is crucial in creating complex social, political, and psychological connotations, based on research findings.